2019
DOI: 10.3389/fneur.2019.00690
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Emergency Department Utilization and Diagnosis for Sports-Related Head Injuries

Abstract: Background: Prior studies have shown racial differences in concussion awareness and outcome. Objective: To assess if racial or ethnic differences exist in Emergency Department (ED) utilization and diagnosis for children with sports-related head injuries. Methods: We performed a retrospective, cross-sectional analysis of ED visits from 2008 to 2017 using National Electronic Injury Surveillance System (NEISS) data. Population-weighted ED visits for child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 28 publications
1
37
1
Order By: Relevance
“…Among youth and adolescent sports participants, Black/ African Americans are less likely to be diagnosed with a concussion compared with White/non-Hispanics. 23 However, Black/African American high school athletes in this study reported having higher symptom severity scores at baseline compared with White/non-Hispanics. There was an approximate difference of 2.5 between race at baseline.…”
Section: Discussioncontrasting
confidence: 53%
“…Among youth and adolescent sports participants, Black/ African Americans are less likely to be diagnosed with a concussion compared with White/non-Hispanics. 23 However, Black/African American high school athletes in this study reported having higher symptom severity scores at baseline compared with White/non-Hispanics. There was an approximate difference of 2.5 between race at baseline.…”
Section: Discussioncontrasting
confidence: 53%
“…TBI is more common in blacks compared to other races due to the fact that high violence rates are seen in black teens [16]. Black children are significantly less likely to have ED visits after a head injury, and less likely to be diagnosed with brain concussion compared to whites [17]. According to a study on children and adolescent hospitalizations, most children with TBI are male and white [18].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11,529,994 injuries for pediatric sport-related injuries, 13% were injuries to the head, and 5.4% of those patients were diagnosed with SRC. 9 African American patients were less likely than Caucasian patients to have ED visits for head injuries or concussions and were less likely to be diagnosed with a concussion during an ED visit. 9 …”
Section: Review Of Evidencementioning
confidence: 92%
“… 9 African American patients were less likely than Caucasian patients to have ED visits for head injuries or concussions and were less likely to be diagnosed with a concussion during an ED visit. 9 …”
Section: Review Of Evidencementioning
confidence: 92%